PENDAMPINGAN UMKM DI KECAMATAN BANGGAI TENGAH KABUPATEN BANGGAI KEPULAUAN DALAM MEMBANGUN EKONOMI LOKAL YANG BERKELANJUTAN - Saudin, La; B.Lule, Hasna; Reny, Ni Putu (Yayasan Education and Social Center, 2024)
Assistance for Micro, Small and Medium Enterprises (MSMEs) in Banggai Tengah District, Banggai Islands Regency, is an effort made to strengthen a sustainable local economy. Through preliminary studies, designing mentoring programs, implementing activities, and monitoring and evaluation, this activity aims to improve the skills, knowledge, and access of MSME owners to markets and the necessary resources. The method of implementing activities involves community participation, collaboration with related parties, application of participatory methods, and development of local capacity. The results of the implementation of activities show a significant increase in MSME skills and access, as well as a positive contribution to local economic growth. However, there are still challenges in implementing the program, such as ensuring sustainability and strengthening cooperation between related parties. Therefore, continuous efforts need to be made to increase the effectiveness and relevance of MSME mentoring programs in order to achieve sustainable local economic development